2011
DOI: 10.1111/j.1365-2095.2011.00865.x
|View full text |Cite
|
Sign up to set email alerts
|

Probiotic bacteria effects on growth and bacterial composition of black tiger shrimp (Penaeus monodon)

Abstract: The effects of Bacillus probiotic forms on growth performance and microbiota were examined in black tiger shrimp (Penaeus monodon). Shrimp were fed for 120 days with one of three diets; a control diet alone or supplemented with either probiotics consisting of live-sprayed Bacillus (LS) or freeze-dried Bacillus (FD). Culturable bacteria counts in the hepatopancreas, intestine and culture water of the three treatments were relatively constant during the experiment. Bacillus numbers in the hepatopancreas and inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 66 publications
(49 citation statements)
references
References 44 publications
5
43
1
Order By: Relevance
“…and microalgae (Tetraselmis sp.). The main probiotic bacteria documented and used in crustacean farming belong to the Bacillus genus (Moriarty 1998;Rengpipat et al 1998;2003;Vaseeharan and Ramasamy 2003;Ziaei-Nejad et al 2006;Decamp et al 2008;Boonthai et al 2011). Other Gram-positive bacteria such as Lactobacillus spp.…”
Section: Main Microorganisms Evaluated and Used As Probiotics In Crusmentioning
confidence: 99%
See 3 more Smart Citations
“…and microalgae (Tetraselmis sp.). The main probiotic bacteria documented and used in crustacean farming belong to the Bacillus genus (Moriarty 1998;Rengpipat et al 1998;2003;Vaseeharan and Ramasamy 2003;Ziaei-Nejad et al 2006;Decamp et al 2008;Boonthai et al 2011). Other Gram-positive bacteria such as Lactobacillus spp.…”
Section: Main Microorganisms Evaluated and Used As Probiotics In Crusmentioning
confidence: 99%
“…(Decamp et al 2008;Boonthai et al 2011), other probiotic species (Wang et al 2005;Wang 2007) or prebiotic supplements Daniels et al 2010;Zhang et al 2011). The other Bacillus species documented so far as probiotics for crustacean are B. licheniformis (Li K. et al 2007), B. coagulans (Zhou et al 2009) and B. pumilus (Hill et al 2009).…”
Section: Bacillus Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…One way analysis of variance (ANOVA) and Duncan's multiple range test (Duncan, 1955) were applied to compare means between two treatments. (Gomezgil, 1995;Rengpipat et al, 2000;Hong et al, 2005;Pooramini et al, 2009;Boonthai et al) Uma (1995), Gabriel, et al, (2002) Venkat, et al (2004) Seenivasan, et al, (2012) have also reported effectiveness of commercially available probiotics to improve growth performance of different crustaceans and fin fishes. The, degree of survivability of probiotic bacteria in the experimental feeds is an important criterion to assess their effect on growth performance of host.…”
Section: Methodsmentioning
confidence: 99%